Badan Pusat Stratistik Kecamatan Anggeraja Kabupaten Enrekang (BPS Enrekang), (2017). Peraturan Pemerintah nomor 78 tahun 2007 tentang Tata Cara Pembentukan, Penghapusan dan Penggabungan Daerah Undang-Undang Dasar Tahun 1945. RPJMD Kabupaten Enrekang 2014 - Taufiqur Rachman; Juswan Sade; Muhammad Zubair M Alie; Hasdinar Umar; Achmad Yasir Baeda; Chairul Paotonan (Faculty of Engineering UNHAS, 2019)
Mode of transport waterway river tallo Makasar has been operated since long transports passengers, luggage and a motor vehicle, and the only access mode for the island lakkang people through tallo to kera-kera, the eastern and the southern of Makassar city. In the operation of waterway mode, the owner ignored the shipping safety of waterway. It was proven that there is not any other safety devices above the waterway mode. Shipping safety device is an absolutely thing must be required for sea transportation, rivers and lakes. Hence it is necessary to disseminate the importance of shipping safety device for the owner of the river tallo makassar to increase the quality of service of shipping safety for passengers mode independently in accordance with national and international regulations. The safety of the device is based on land transport minister regulation no. PM 25 years 2015, transportion safety standards on the river lakes and crossing. Disseminate gives users of security and safety and public service quality shipping safety for passengers in the river tallo makassar when sailing and the process of loading and unloading of passengers and a motor vehicle.